Oral Contraceptives, Hormone Replacement Therapy and Thrombosis - Rosendaal, F. R.; Helmerhorst, F. M.; Vandenbroucke, J. P. (Thrombosis and Haemostasis, 2001)
Oral contraceptives and hormone replacement therapy are used by hundreds of millions of women worldwide. Since the early 1960s it is known that female hormones increase the risk of venous thrombosis, myocardial infarction and stroke. This risk is still present with current low-dose oral contraceptives and, even though in absolute terms the risk is small, oral contraceptives form the major cause of thrombotic disease in young women. The risk is higher during the first year of use (up to 1 per 1000 per year), with the use of desogestrel- or gestodene-containing oral contraceptives (“third generation progestogens”) and among women with a prothrombotic predispositon. Hormone replacement therapy increases the risk of venous thrombosis, while results of randomised trials so far do not substantiate the expectation of a beneficial effect on the risk of arterial cardiovascular disease. First results are emerging that specific subgroups of women, with prothrombotic or other abnormalities, may be at risk, especially during the first years of use of hormone substitution.
Keywords: Venous thrombosis; myocardial infarction; stroke; oestrogens; progestogens; oral contraceptives; hormone replacement therapy